Climate Complicity and Individual Accountability. (20th December 2018) - MacLean, Douglas
Abstract: Climate change is a unique ethical problem. The individual actions of virtually everyone in the world contribute to climate change, which risk causing great harm, especially in the future. We are all complicit in causing this harm. In most cases, complicity implies accountability: one deserves blame or punishment, he becomes a legitimate subject of reactive attitudes, or he owes compensation. I argue that individuals are not accountable in these ways for their complicity in causing climate change. Rather, our moral accountability flows directly to our political and collective responsibility. A morally decent person living in a developed, carbon-based society has no moral obligation to change the way she lives, but we all have strong moral duties to pressure our governments (and large corporations and institutions) to enact effective policies to limit carbon emissions.